Pengaruh Beasiswa Kartu Indonesia Pintar (KIP) Terhadap Kesenjangan Sosial Melalui Aksesibilitas Pendidikan - Dewi Ulfah Ningsih; Hasbiah (At-Thariqah: Jurnal Ekonomi, 2024)
This research discusses the influence of KIP scholarships on social inequality through educational accessibility. The aim of this research is to determine the effect of KIP scholarships on social inequality through the educational accessibility of students receiving KIP scholarships at IAIN Sorong. This type of research is associative causal. The sample in this research was 84 students from the sharia economics study program in the 2020-2022 class. The data in the research were analyzed using the IBM SPSS version 27 application, then the data was obtained through a closed questionnaire using the Google form application. The results of this research show the influence of KIP scholarships on educational accessibility. The results of this research show the influence of KIP scholarships on social inequality. The results of this research show the influence of educational accessibility on social inequality. Then the results of this research show the influence of KIP scholarships on social inequality through educational accessibility.